MAKNA AL-ARD DALAM AL-QUR’AN (Kajian Semantik Juz 28) - Arifin, Ali Zainal; Aisyah, Aas Siti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Ilmu Al-Qur'an Al Multazam Kuningan, 2021)
Abstract This study discusses the meaning of the word al-ar? in the Qur'an juz 28. The word al-ar? is closely related to human life, namely with human habitation, in the translation of the Qur'an it only provides an initial description of the meaning of al-ar?, so it requires a more in depth explanation in order to know its meaning comprehensively. This study uses Toshihiko Izutsu semantic theory of the Qur'an in order to know its meaning comprehensively. The stages carried out in this research are to find the basic meaning, relational meaning using syntagmatic and paradigmatic analysis, then examine the historical meaning seen from the synchronic and diachronic aspects, and the last is to look for weltanschauung or the conceptual meaning of the word al-ar?. Which of these studies shows that the word al-ar? in juz 28 is divided into two meanings namely, the meaning of the earth in general (Ithl?qu al-ma'?n?) and the seventh earth (sab'i ara??n). These two meanings lead to the world view of the Qur'an or weltanschauung to the word al-ar? which means the earth as a human habitation.